(untitled) (The Pretoria Student Law Review, 2023)
Sport undeniably plays a major role in society today. Over the years, it has developed into n free-standing industry and its players have become increasingly valuable and earn income both on and off the field. This article addresses the income generated by sport stars off the field of play through the exploitation of their ‘image rights’. The use of someone’s image rights can be explained as the practice of appropriating someone’s personality. In modern society, people have become transfixed by sport stars. This has led to the image rights of individual sport stars such as Lionel Messi and Cristiano Ronaldo to become commodities exploited by their clubs and other third parties to enhance brand images and promote the sale of products.1 This use of the image rights of celebrities generates a whole new source of income for these sport stars. Due to the relatively high amounts of income received for the use of a sport star’s image, these stars may be tempted to enter into creative schemes in an attempt to reduce high taxes levied against these streams of income. The practice of the commercial exploitation of a sport star’s image rights is a relatively new development in South Africa and is not yet recognised to the same extent as in other jurisdictions, such as the UK and Spain. This article examines the existing South African sport, intellectual property, and tax laws governing image rights and specifically analyses whether South Africa is sufficiently equipped, under tax legislation, to address these minimisation schemes aimed at reducing the tax liability arising from a South African sport star’s image rights.